Pojav fizičnega nasilja nad medicinskimi sestrami na delovnem mestu - Košir, Irena (Obzornik zdravstvene nege, 2012)
Introduction: Ensuring patient's physical and emotional safety and quality of care is one of the primary concerns of a nurse. It requires a safe working environment for nurses where they can practice without fear or threat of aggression. The aim of the study was to determine the prevalence and nature of the perceived and experienced violence against nurses and identify the primary perpetrators of violence. A correlation between workplace violence, the nurses' educational level and workplace was explored. Methods: The research was implemented from November 2010 to February 2011. The data were collected through a questionnaire developed for the purpose of the research and distributed among 3756 (20 %) Slovenian nurses. 692 (18.4 %) questionnaires were completed and returned. The article presents only those results which address physical violence at a workplace. Results: Statistically significant differences have been established between the perceived (chi-square = 42.2, p < 0.001) and experienced physical violence (chi-square = 25.6, p < 0.001). The highest incidence of workplace violence against nurses, perceived (53.3 %) and experienced (33.3 %), occurs in outpatient emergency units. The results of the study indicate also that there is a correlation between nurses' educational level and experienced physical violence (chi-square = 4.33, p = 0.05). 16.9 % of nursing technicians and 11.2% of nurses with higher education have been exposed to this form of violence. Most commonly the perpetrators are the patients (74.8 %). Nurses listed different violent acts directed towards them at work or on duty, such as punching, kicking, pushing, and similar. Discussion and conclusions: Results of the study suggest that violence against nurses is especially pronounced in outpatient emergency departments and in homes for the elderly where nurses provide care for patients with specific health conditions. Unsafe conditions in workplaces may jeopardize the quality of patient care. A thorough research of recognition of different forms of physical violence should therefore be developed along with policies and procedures for reporting violent events and instituted victim protection.
Keywords: education; fizično nasilje; forms of physical violence; medicinske sestre; nasilje; nasilje na delovnem mestu; nurses; perpetrators; storilci; workplace violence; workplaces